2012
DOI: 10.2967/jnumed.112.109470
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Tumor Volume Predicts Disease Progression and Survival in Patients with Squamous Cell Carcinoma of the Anal Canal

Abstract: PET imaging has become a useful diagnostic tool in patients with anal cancer. We evaluated the prognostic value of metabolic tumor volume (MTV) in patients with anal cancer treated with definitive chemoradiotherapy. Methods: Patients with anal cancer who underwent PET imaging for pretreatment staging or radiation therapy planning from 2003 to 2011 were included. PET parameters included MTV and maximum standardized uptake value (SUVmax). Total MTV (MTV-T) was defined as the sum of the volumes above a standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…In this regard, other studies in lung, oesophageal, head and neck and cervical cancers showed that higher SUVmax correlates with worse local control and diseasefree survival rate [20,21,28,29]. On the other hand, the more recent study of Bazan et al, similarly to us, found no correlation between SUVmax and DFS and OS in a sample of 39 patients [25]. In clinical practice, SUVmax is considered the most reproducible parameter that can estimate metabolic activity of FDG uptake.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…In this regard, other studies in lung, oesophageal, head and neck and cervical cancers showed that higher SUVmax correlates with worse local control and diseasefree survival rate [20,21,28,29]. On the other hand, the more recent study of Bazan et al, similarly to us, found no correlation between SUVmax and DFS and OS in a sample of 39 patients [25]. In clinical practice, SUVmax is considered the most reproducible parameter that can estimate metabolic activity of FDG uptake.…”
Section: Discussionmentioning
confidence: 75%
“…The present study did not show a significant direct correlation between SUVmax and DFS and OS. In this regard, other literature studies [24,25] on the use of SUVmax in anal cancer reported controversial results. Kidd et al did not find higher baseline SUVmax significantly associated with an increased risk of persistent disease.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations